Mental Load Analysis Using NASA-TLX on Production Operators at PT. Cemindo Gemilang North Sumatra - Zulvia, Reakha; Sitompul, Andre Josua (CV. Publikasi Indonesia, 2025)
Workload is a job demand that arises from receiving orders or requests, which directly impacts an individual's performance. Mental workload can be influenced by various factors, such as overtime, poor social relations between departments, and environmental conditions like low temperatures. This study aims to determine both the minimum and maximum mental workload and identify the contributing factors using the NASA Task Load Index (NASA TLX) and Cardiovascular Load (CVL) method. The research focuses on measuring the subjective mental workload of employees, particularly in a production environment. Using the NASA TLX method, six indicators—mental demand, physical demand, temporal demand, performance, effort, and frustration—were assessed and scored. Additionally, the CVL method was employed to measure cardiovascular load as an objective measure of mental workload. The findings suggest that certain factors, including extended working hours, interdepartmental communication issues, and environmental conditions, significantly contribute to high mental workload. This study provides insight into the key factors influencing mental workload, offering valuable recommendations for reducing workload-related stress in the workplace and enhancing employee well-being. Future research could expand on these findings by exploring specific interventions to address identified causes.